2019
DOI: 10.18805/ijare.a-395
|View full text |Cite
|
Sign up to set email alerts
|

Effect of urea, bio-fertilizers and their interaction on the growth, yield and yield attributes of Cyamopsis Tetragonoloba

Abstract: A field experiment was conducted at Agriculture Research Station Bahawalpur (Pakistan) during Kharif, 2016 to evaluate the response of cluster bean against bio and chemical fertilizers. The treatments consisted of three levels of nitrogen (urea 75g, 85g and 95g/40g seeds) with three level of Rhizobium (1.5g, 2.0g and 2.5g/40g of seeds). The experiment arranged in a randomized complete block design with 16 treatments and three replications. Combine treatment of urea and Rhizobium resulted in maximum plant heigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…AM fungi inoculated seedlings of Eucalyptus tereticornis showed 95% survival over the control seedlings and their growth was also significantly higher in bauxite mine spoil (Karthikeyan and Krishnakumar, 2012). Study by Gul et al (2019), also supported our results where growth of guar responded well towards the consortium of bioinoculants and inorganic fertilizers. Hence, these bioinoculants were found to be effective in reviving the soil health and plant development and growing plants together with rhizobacteria and AMF in feldspar mine spoils stimulated the plant germination, shoot as well as root growth.…”
Section: Growth Parameterssupporting
confidence: 87%
“…AM fungi inoculated seedlings of Eucalyptus tereticornis showed 95% survival over the control seedlings and their growth was also significantly higher in bauxite mine spoil (Karthikeyan and Krishnakumar, 2012). Study by Gul et al (2019), also supported our results where growth of guar responded well towards the consortium of bioinoculants and inorganic fertilizers. Hence, these bioinoculants were found to be effective in reviving the soil health and plant development and growing plants together with rhizobacteria and AMF in feldspar mine spoils stimulated the plant germination, shoot as well as root growth.…”
Section: Growth Parameterssupporting
confidence: 87%
“…They also reported the higher amount of chlorophyll in mustard plants treated with B. megaterium (mj1212) as compared to untreated plants. Similarly, Gul et al (2019) reported significant increase of chlorophyll content along with other growth parameters in a combined treatment of urea and Rhizobium sp. in Cyamopsis tetragonoloba.…”
Section: Measurement Of Total Chlorophyllmentioning
confidence: 74%
“…Biofertilizers help in making the soil environment rich in all kinds of micro-and macro-nutrients via number of processes such as nitrogen fixation, mineralization as phosphate and potassium solubilization, release of plant growth regulating substances, production of antibiotics and biodegradation of organic matter in the soil (Sinha et al, 2014;Sivakumar et al, 2013) which provide efficient nutrient uptake and help in improving plant tolerance towards drought and moisture stress (Abdelraouf et al 2013). Sometimes combine treatment of urea and Rhizobium resulted in maximum plant growth as seen in cluster bean (Gul et al 2019). In India Rhizobium was the first microbial inoculant, which was introduced as biofertilizer in the beginning of the seventies with the introduction of soybean into the country.…”
Section: Introductionmentioning
confidence: 99%